Single Immunization of a Vaccine Vectored by a Novel Recombinant Vaccinia Virus Affords Effective Protection Against Respiratory Syncytial Virus Infection in Cotton Rats - Russell, Marsha S.; Thulasi Raman, Sathya N.; Gravel, Caroline; Zhang, Wanyue; Pfeifle, Annabelle; Chen, Wangxue; Van Domselaar, Gary; Safronetz, David; Johnston, Michael; Sauve, Simon; Wang, Lisheng; Rosu-Myles, Michael; et al. (Frontiers in Immunology, 2021)
Respiratory syncytial virus (RSV) is a leading cause of respiratory infections worldwide and disease management measures are hampered by the lack of a safe and effective vaccine against the infection. We constructed a novel recombinant RSV vaccine candidate based on a deletion mutant vaccinia virus platform, in that the host range genes E3L and K3L were deleted (designated as VACVΔE3LΔK3L) and a poxvirus K3L ortholog gene was used as a marker for the rapid and efficient selection of recombinant viruses. The safety of the modified vaccinia virus was investigated by intranasal administration of BALB/c mice with the modified vaccinia vector using a dose known to be lethal in the wild-type Western Reserve. Only a minor loss of body weight by less than 5% and mild pulmonary inflammation were observed, both of which were transient in nature following nasal administration of the high-dose modified vaccinia virus. In addition, the viruses were cleared from the lung in 2 days with no viral invasions of the brain and other vital organs. These results suggest that the virulence of the virus has been essentially abolished. We then investigated the efficiency of the vector for the delivery of vaccines against RSV through comparison with another RSV vaccine delivered by the widely used Modified Vaccinia virus Ankara (MVA) backbone. In the cotton rats, we found a single intramuscular administration of VACVΔE3LΔK3L-vectored vaccine elicited immune responses and protection at a level comparable to the MVA-vectored vaccine against RSV infection. The distinct features of this novel VACV vector, such as an E3L deletion for attenuation and a K3L ortholog for positive selection and high efficiency for vaccine delivery, could provide unique advantages to the application of VACV as a platform for vaccine development.